Implementasi Strategi Regional Chaser Dan Local Champion Plus Global Market Online Pada Industri Spesial âGreen Batikâ Dan Interpreneurs Building Di Jawa Tengah - Rasiman, Rasiman; Prayito, Muhammad; Tsalatsa, Ahmad Nasir (JIU, 2016)
Abstract - Batik has various motives and its manufacture for basic materials. In mathematics kinds of batik motif can be made easily and pull through some mathematical concepts. Batik motifs that evolve at this point is still quite monotonous. In order motif sell high value, it can be modified to become more attractive in accordance with a pattern emerging at this time. The research objective is (1) make creative engineering design green batik motif, (2) maximize marketing with the implementation of regional strategies and local champion chaser plus global online market, and (3) maximizing the potential of local knowledge so as to boost the economy in some areas in Central Java. This research approach, focuses on the empowerment of exploiting Information and Communication Technology in the creation of batik motif design and marketing to penetrate the international market. Research result : (1) batik craftsmen can design green batik motif with lots of patterns and shades, (2) some craftsmen used to market batik online, and (3)increasing the communitys economy âbatikâ artisans in some areas. Keyword: Regional Chaser, Local Champion, Global Market Online, Green Batik.